Effectiveness of Mobilization Mat on Decubitus Incidents in Patient on Bed Rest Due to Stroke at West Java Regional Hospital - Anah Sasmita; Sugiyanto Sugiyanto; Peni Cahyati; Metilda Metilda (International Journal of Psychology and Health Science, 2026)
Pressure ulcers are a common complication among bedridden stroke patients, leading to pain, infection, prolonged hospitalization, and reduced quality of care. These injuries result from sustained pressure that impairs blood circulation and causes tissue damage. Major risk factors include immobility, prolonged pressure, skin moisture, malnutrition, and the inability to change body position independently. This study aimed to analyze the effectiveness of the Pastibar patient mobilization mat (Alasmob Pastibar) in preventing pressure ulcers among bedridden stroke patients at the West Java Regional General Hospital. A quasi-experimental pretest–posttest design with a control group was employed. The sample consisted of 80 respondents selected through purposive sampling and divided equally into intervention and control groups. Data were collected through direct observation and questionnaires assessing patients’ skin conditions before and after seven days of treatment. Statistical analyses were conducted using the Wilcoxon and McNemar tests. The findings demonstrated that Alasmob Pastibar significantly enhanced patient mobilization and reduced the incidence of pressure ulcers compared to conventional care (p < 0.05). In the intervention group, 88% of patients did not develop pressure ulcers, whereas 75% of patients in the control group experienced pressure ulcers. Additionally, patients using Alasmob Pastibar reported lower pain complaints, and nursing staff required less time to reposition patients. These results indicate that Alasmob Pastibar is an effective tool for preventing pressure ulcers in bedridden stroke patients by improving comfort, reducing injury risk, and facilitating patient mobilization. Therefore, its implementation in nursing practice is recommended to enhance the quality of care for bedridden patients. Further studies involving larger populations and longer observation periods are recommended to validate and strengthen these findings.